2007
DOI: 10.1080/10640260701454337
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emotional Abuse in the Eating Disorders: Implications for Treatment

Abstract: This paper addresses the clinical links between emotional abuse and the eating disorders. It is argued that the core feature of a range of abusive experiences is emotional invalidation. Emotional abuse is associated with problems in the development of emotional skills, manifesting as alexithymia, poor distress tolerance, and emotional inhibition. Cognitive-behavioral approaches are outlined for work with eating-disordered patients with a history of emotional abuse. As well as addressing the central concerns ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 23 publications
4
37
0
2
Order By: Relevance
“…10 In addition, clinicians might find it useful to identify the underlying factors that might be associated with an unwillingness to express emotions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In addition, clinicians might find it useful to identify the underlying factors that might be associated with an unwillingness to express emotions.…”
Section: Discussionmentioning
confidence: 99%
“…The development of these attitudes is often seen as the consequence of invalidating environments during childhood, where expression of feelings is either prohibited or ignored. 6,10 These types of attitude have been associated with the development of post-traumatic stress disorder (PTSD) and increased emotional distress following negative life events. 9,11 In further support of these findings, a reluctance to confide in others (thereby retaining emotionally distressing information) has also been linked to poor mental health, 12,13 while accepting social support has been linked to positive mental health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Anorectic behaviour has, however, been described as inducing positive feelings such as mastery and control and pride . Corstorphine and colleagues found that women with eating disorders were more likely to avoid situations that could provoke positive as well as negative affect (Corstorphine et al, 2007). Furthermore, several recent studies suggest a close relation between avoidance of positive affect and eating disorder behaviours (Lampard, Byrne, McLean, & Fursland, 2011;Raykos, Byrne, & Watson, 2009).…”
Section: Further Researchmentioning
confidence: 99%
“…Several theoretical models suggest that eating disorder behaviour serves as a means to regulate affect Skarderud & Fonagy, 2011;Waller, Corstorphine, & Mountford, 2007). Binge-eating has been regarded as a way to escape aversive self-awareness or block painful emotions .…”
Section: Introductionmentioning
confidence: 99%
“…At the current time, the examination of DT in clinical populations has been limited mostly to adults. Specifically, research has focused on how individuals with low levels of DT may have an inability to handle exposure to negative emotions caused by smoking cessation (Brown, Lejuez, Kahler & Strong, 2002;Brown et al, 2005); abstinence from drugs and alcohol Daughters, Lejuez, Bornovalova, et al, 2005); treatment for eating disorders (Anestis, Selby, Fink & Joiner, 2007;Waller, Corstorphine, & Mountford, 2007); and cessation of self-harm behaviors in individuals with BPD (Gratz, 2003).…”
Section: Dt and Psychopathologymentioning
confidence: 99%